In vivo antiestrogenic activity of mifepristone in the rat - Nedvídková, J; Schreiber, V; Stárka, L (Journal of endocrinological investigation, 1997)
The aim of this study was to find out whether mifepristone, known mainly as a substance with an antiprogesterone and antiglucocorticoid effect, also has an in vivo antiestrogenic activity on the adenohypophysis of the rat. Male Wistar rats were given chronically either estradiol-benzoate (EB, 1 mg s.c. twice a week) for a period of 12 days, or the non steroidal antiestrogen tamoxifen (1 mg/day/rat), or mifepristone (1 mg/day/rat), or EB together with mifepristone or tamoxifen. The hypertrophic effect of the EB on the weight of the adenohypophysis (AP) was significantly suppressed both by tamoxifen and by mifepristone. Mifepristone and tamoxifen reduced the increased content of PRL in the estrogenized adenohypophysis. Mifepristone but not tamoxifen significantly increased the content of the LH in the adenohypophysis of estrogen treated rats. Mifepristone and tamoxifen suppressed the increased concentration of cyclic nucleotides cAMP and cGMP in the estrogenized adenohypophysis. Mifepristone given alone increased serum levels of corticosterone, but when given together with EB deepened inhibiting effect EB on them. The results of our preliminary study show that mifepristone exerts a weak antiestrogenic activity on the level of hypophysis, however the pharmacology is not identical to tamoxifen.
Keywords: kortikosteron; velikost orgánu; Estrogen Antagonists; fixní kombinace léků; estradiol; injekce subkutánní; Corticosterone; Tamoxifen; krysa rodu Rattus; zvířata; potkani Wistar; Injections, Subcutaneous; tamoxifen; Pituitary Gland, Anterior; Estradiol; Rats, Wistar; Male; mifepriston; adenohypofýza; Mifepristone; Rats; Body Weight; Animals; Organ Size; tělesná hmotnost; mužské pohlaví; Drug Combinations; antagonisté estrogenu